2009
DOI: 10.2746/042516408x345116
|View full text |Cite
|
Sign up to set email alerts
|

Diseases in neonatal foals. Part 1: The 30 day incidence of disease and the effect of prophylactic antimicrobial drug treatment during the first three days post partum

Abstract: The results provide an up-to-date overview about the frequencies of various neonatal foal diseases. They do not support the traditional prophylactic use of antimicrobials to prevent infectious diseases in healthy newborn foals. However, it should be noted that this study was not a randomised controlled trial and therefore does not provide the strongest possible evidence for this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 17 publications
4
40
2
4
Order By: Relevance
“…Bacteria may gain access through the umbilicus or respiratory or gastrointestinal tract, resulting in a bacteremia. When IgG is routinely assessed and Hypermune equine plasma (Veterinary Immunogenics Ltd., Penrith, United Kingdom) is administered to foals with IgG <400 mg/dL, the cumulative incidence of osteomyelitis within the first 30 days is 0.2% [2]. In foals less than 6 months of age with septic osteomyelitis, the femur, distal phalanx, and tibia are the most commonly affected sites, accounting for 55% of cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria may gain access through the umbilicus or respiratory or gastrointestinal tract, resulting in a bacteremia. When IgG is routinely assessed and Hypermune equine plasma (Veterinary Immunogenics Ltd., Penrith, United Kingdom) is administered to foals with IgG <400 mg/dL, the cumulative incidence of osteomyelitis within the first 30 days is 0.2% [2]. In foals less than 6 months of age with septic osteomyelitis, the femur, distal phalanx, and tibia are the most commonly affected sites, accounting for 55% of cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…The infections of internal umbilical structures that develop during the neonatal period have been associated with inflammation in different parts of the body and with generalised septicaemia (Brewer and Koterba 1988, Bryant and Gaughan 2005). Omphalitis was observed in 13 per cent of foals with septicaemia (Gayle and others 1998), while in 2009 researchers found an incidence of 0.71 per cent in a group of Thoroughbred foals in UK (Wohlfender and others 2009a). Most affected foals are between one and eight weeks old (Adams and Fessler 1987), moreover one study suggested that foals born in March are at increased risk of developing systemic disease due to stress caused by overcrowding (Wohlfender and others 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Given that omphalitis and its complications cause huge economic losses in horse breeding (Horohov 2005, Wohlfender and others 2009a), the objectives of this study were to evaluate the bacteria involved in equine omphalitis and their susceptibility to antimicrobial drugs, and to provide guidelines concerning the most suitable treatment protocol on the basis of ultrasonography and clinical and bacteriological examination.…”
Section: Introductionmentioning
confidence: 99%
“…La incidencia en la falla en la absorción de Ig (IgG < 400mg/dl) fue del 14,58 % en potros de raza criollo colombiano en este estudio, resultados que se encuentran dentro de los rangos registrados en la literatura, que van del 2,9 al 25 % (1,11,35). La falla en la absorción está relacionada con incrementos en las tasas de mortalidad de potros neonatos (OR: 63; p < 0,01) (7), al dejar expuesto al potro para la adquisición de entidades de origen infeccioso.…”
Section: Discussionunclassified
“…Las entidades infecciosas y las deformidades angulares han sido identificadas como las principales causas de enfermedad y muerte (1,2,4,5). En este estudio se encontró que la enfermedad respiratoria con fiebre (4,9 casos/100 potros/año), la diarrea con fiebre (3,9 casos/100 potros/año) y las deformidades angulares y flexurales (3,2 casos/100 potros/año) fueron las enfermedades más frecuentes, lo cual se asemeja a lo encontrado en diferentes estudios.…”
Section: Discussionunclassified